Adsorption of Remazol Brilliant Blue Dye Using Palm Oil Shell Fly Ash HCl Activated - Lestari, Intan; Azira, Ayu; Farid, Faizar (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
Remazol Brilliant blue is an azo dye that is widely used in textile dyeing. The most appropriate handling method to be used in overcoming problems caused by textile dye waste is adsorption. Fly ash is an adsorbent that can be used to overcome this problem. Chemical activation was carried out using 1 M HCl solution. Besides that, physical activation was also carried out at 500Â°C for 1 hour. Research is needed to determine the optimum conditions for fly ash in dye adsorption to produce high adsorption efficiency. XRF characterization showed that palm shell fly ash was dominated by CaO of 71.064% and SiO2 of 15.734%. Characterization using FTIR shows the presence of Si-O groups in Fly ash. To analyze the surface morphology of the fly ash adsorbent, an SEM test was carried out and it was known that the surface morphology of the fly ash adsorbent after chemical and physical activation showed pore formation. Characterization using Surface Area Analyzer showed a surface area of 13.6153 m2/g. optimum absorption conditions at pH 6 with an adsorption capacity of 15.84 mg/g. optimum contact time of 60 minutes with an adsorption capacity of 15.54 mg/g. The optimum adsorbent mass is 0.5 g with an adsorption capacity of 9.54 mg/g and the optimum adsorbent concentration is at 200 ppm with an adsorption capacity of 69.08 mg/g. In this study the adsorption model used is the Freundlich isotherm. Based on the research result, it is known that fly ash is a suitable adsorbent for dye adsorption which is characterized by high color removal efficiency. Further characterization regarding the initial conditions of fly ash is needed as a comparison for fly ash after activation